Measuring the reliability of wheelchair user route planning based on volunteered geographic information - Neis, Pascal (Transactions in GIS, 2015)
The development of a wheelchair user friendly route planning application inherits a number of special requirements and details that need to be considered during the generation of the routing graph an...
First published: 17 April 2014
Gesehen am 17.08.2020